Response Evaluation Criteria in Cancer of the liver version 6 (Response Evaluation Criteria in Cancer of the Liver 2021 revised version). Issue 4 (22nd February 2022) - Kudo, Masatoshi; Ikeda, Masafumi; Ueshima, Kazuomi; Sakamoto, Michiie; Shiina, Shuichiro; Tateishi, Ryosuke; Nouso, Kazuhiro; Hasegawa, Kiyoshi; Furuse, Junji; Miyayama, Shiro; Murakami, Takamichi; Yamashita, Tatsuya; et al.
Abstract: Response Evaluation Criteria in Solid Tumors (RECIST) is inappropriate to assess the direct effects of treatment on hepatocellular carcinoma (HCC) by locoregional therapies, such as radiofrequency ablation or transarterial chemoembolization. Therefore, establishment of response evaluation criteria solely devoted to HCC is needed in clinical practice, as well as in clinical trials of HCC treatment, such as systemic therapies, which cause necrosis of the tumor. Response Evaluation Criteria in Cancer of the Liver (RECICL) was revised in 2021 by the Liver Cancer Study Group of Japan based on the 2019 version of RECICL, which was commonly used in Japan. The major revised points of the RECICL 2021 is inclusion of RECIST version 1.1 and modified RECIST as response evaluation criteria in systemic therapy for HCC. We hope this new treatment response criteria, RECICL, proposed by the Liver Cancer Study Group of Japan will benefit the HCC treatment response evaluation in the setting of daily clinical practice and clinical trials as well, not only in Japan, but also internationally.